Venezuelan migrants and access to contraception in Colombia: A mixed research approach towards understanding patterns of inequality - Juan Carlos Rivillas-García; Ángela Cifuentes-Avellaneda; Johan Sebastián Ariza-Abril; Marcela Sánchez-Molano; Danny Rivera-Montero (Elsevier, 2021)
Background: Migration should not put at risk the achievements of SDG 3: Universal Access to Sexual and Reproductive Healthcare, particularly access to contraceptive methods for Venezuelan migrants in receiving countries such as Colombia. Each year, more than 2 million men and women have access to modern contraceptive methods in Colombia. However, amid the pandemic, disruptions in supply chains, the interruption of essential services for sexual and reproductive health, and social inequalities may jeopardize these gains in contraception among Venezuelan migrants and refugees. The measurement of inequalities focuses on identifying the epicenter of inequity that is particularly relevant within the humanitarian response under strain. The objective of this article is to identify inequalities in access to contraception services among the migrant and refugee populations in six cities that concentrate 70% of the Venezuelan migration into Colombia and to discuss the challenges they represent for future emergencies. Methods and findings: We used a cross-sectional, descriptive study that included a mixed research approach (quantitative and qualitative analyses) based on three activities: i) analysis of contraceptive care records for the period 2018-2019; ii) measurement of inequalities in access to contraceptive services, and iii) design and implementation of twelve focus groups among Venezuelan migrants and refugees for discussion. Results: Despite the evidence of a 70% increase in the use of contraceptive services among Venezuelan migrants between 2018 and 2019, there are absolute and relative inequalities in access to contraceptive methods both in the migrant and refugee populations versus the host population. The inequalities are mainly explained by the demographic dependency rate and the lack of job opportunities. Conclusions: The provision of essential sexual and reproductive health services to migrant and host populations must be regular, continuous, and shielded so that under no circumstances is it interrupted neither for infectious disease outbreaks to climate change emergencies in the future.